1998
DOI: 10.1006/jmva.1998.1741
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Estimation of the Measurement Error Model Using Multiple Indicators

Abstract: This paper considers the nonparametric estimation of the densities of the latent variable and the error term in the standard measurement error model when two or more measurements are available. Using an identification result due to Kotlarski we propose a two-step nonparametric procedure for estimating both densities based on their empirical characteristic functions. We distinguish four cases according to whether the underlying characteristic functions are ordinary smooth or supersmooth. Using the loglog Law an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
257
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(260 citation statements)
references
References 7 publications
3
257
0
Order By: Relevance
“…This result has been used in many empirical and theoretical studies, such as Li and Vuong (1998), Li, Perrigne, and Vuong (2000), Krasnokutskaya (2011), Schennach (2004a), and Evdokimov (2010.…”
Section: A 2-measurement Modelmentioning
confidence: 94%
“…This result has been used in many empirical and theoretical studies, such as Li and Vuong (1998), Li, Perrigne, and Vuong (2000), Krasnokutskaya (2011), Schennach (2004a), and Evdokimov (2010.…”
Section: A 2-measurement Modelmentioning
confidence: 94%
“…Using this assumption, along with a regularity condition from work in nonparametric deconvolution methods by Li and Vuong (1998), they showed that the CIPV model is nonparametrically identified from a sample of bids. Moreover, CIPV can rationalize a sample of bids if and only if the inverse-bid function is monotonic.…”
Section: Conditionally Independent Private Informationmentioning
confidence: 99%
“…The authors' estimation procedure combined methods developed by GPV with those of Li and Vuong (1998). Specifically, in the first stage of estimation they constructed a pseudo-sample of private signals using the inverse-bidding function and nonparametric estimates of the bid distributions.…”
Section: Conditionally Independent Private Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…(In classical measurement error problems, the distribution of the error can be identified from repeated measurements via a Kotlarski-type equality [Schennach (2004), Li and Vuong (1998)]. However, such results do not yet exist for Berkson-type measurement error.)…”
mentioning
confidence: 99%